Exploring the use of Enterprise Content Management Systems in replication types of organizations - Arshad, N.I. (2013)
Depending on the nature of businesses, the use of ECMS can be very different from one organization to another. However, current understanding on why and how such variation exists is limited. Therefore, the aim of this paper is to better understand how highly standardized businesses known as replication organizations use ECMS to support their business processes. This research takes a view that there is an interaction between organizational context, ECMS technologies and users that shaped the ways ECMS are used. A case study approach was used to study this interaction in two replication organizations. Arising from these case studies are insights into the differing interactions that occur between institutional, interpretive and technological conditions that shaped ECMS-use. Based on the comparisons of the two cases, this study has concluded that replication organizations may use ECMS in three ways, for: (1) information sharing that supports a standardized process structure, (2) building custom workflows that support standardized processes, and (3) analysis and decision making. These findings make a significant contribution in such that there is a guide for organizations that are highly standardized to support employees in achieving their intended ECMS-use, to understand reasons for ECMS failures and underutilization and to exploit technologies investments. Â© 2013 IEEE.